2010
DOI: 10.1002/nbm.1495
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and sex‐related differences in muscle phosphocreatine and oxygenation kinetics during high‐intensity exercise in adolescents and adults

Abstract: AND KEYWORDSThe aim of this investigation was to examine the adaptation of the muscle phosphates (e.g. PCr and ADP) implicated in regulating oxidative phosphorylation, and oxygenation at the onset of high intensity exercise in children and adults. The hypotheses were threefold: primary PCr kinetics would be faster in children than adults; the amplitude of the PCr slow component would be attenuated in children; and the amplitude of the HHb slow component would be reduced in children. Eleven children (5 girls, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 55 publications
0
31
0
2
Order By: Relevance
“…Willcocks et al . () also observed that the matching of oxygen delivery to oxygen demand was superior in males relative to females during quadriceps exercise. Exercise efficiency in females compared with males requires further investigation.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Willcocks et al . () also observed that the matching of oxygen delivery to oxygen demand was superior in males relative to females during quadriceps exercise. Exercise efficiency in females compared with males requires further investigation.…”
mentioning
confidence: 82%
“…Willcocks et al . () have documented that the [PCr] cost per watt was higher in females than males in the quadriceps muscle. This may suggest either decreased oxidative capacity or impaired exercise efficiency among females.…”
mentioning
confidence: 99%
“…Two studies of responses to high-intensity constant work rate exercise have not identified statistically significant age69 or maturational70 differences in metabolic responses but large SDs, small sample sizes and differences of ∼42–66% between groups in end-exercise PCr or PCr kinetics during exercise infer possible biological significance.…”
Section: Pulmonary Oxygen Uptake Kinetics and Muscle Phosphocreatine mentioning
confidence: 99%
“…Muscle deoxygenation has been investigated after training in children (Marwood et al., ), and HHb data suggested that training induced faster VO 2p kinetics in trained children were due to the enhancements in both central (oxygen delivery) and peripheral (oxygen utilization) mechanisms (Marwood et al., ). Other studies investigated muscle deoxygenation in children (Barker et al., ; Willcocks et al., ) but did not compare this population to adults at the onset of moderate‐intensity exercise in order to clarify the mechanisms responsible of potential VO 2p kinetics differences between the two populations.…”
mentioning
confidence: 99%